Impacts of a medical-legal partnership on clinical capacity to address social determinants of health. Issue 11 (26th August 2022) - Davis, Kara; Fair, Melissa L; Buckingham, Catie; McKinnon, Hannah; Theriot Roley, Laurie; Sease, Kerry
Abstract : Background: Social determinants of health (SDOHs) impacts on an individual's health outcomes have become more evident, and clinical providers are vital in helping patients address those needs. Providers are experiencing high-stress levels related to patient care, resulting in a diminished capacity to address these SDOHs. This study examines the impact of a medical-legal partnership (MLP) on the clinical capacity to assist providers with addressing SDOH needs and reducing clinician stress. Methods: A 16-question survey was emailed to 532 providers in a local health system. The survey assessed clinicians' perception of their role in addressing SDOH needs, the MLP's impact on their clinical capacity and the MLP's ability to remedy patient SDOH needs. Results: Providers who have referred to the MLP indicated higher levels of agreement that SDOH screenings were part of their clinical responsibility and had higher levels of agreement regarding comfort levels for completing SDOH screenings. Geriatric providers reported higher levels of agreement that the MLP reduced clinician stress than paediatric providers. Conclusion: MLPs have the potential to reduce clinician stress and burnout by standing in the gap to assist providers in addressing their patient's SDOH needs.